2022
DOI: 10.1371/journal.pntd.0010884
|View full text |Cite
|
Sign up to set email alerts
|

Preconception syphilis seroprevalence and association with duration of marriage and age among married individuals in Guangdong Province, China: A population-based cross-sectional study

Abstract: Background Duration of marriage (DoM) and age are important characteristics of married individuals, who are the critical population for eliminating mother-to-child transmission (MTCT) of syphilis. A deep understanding of the preconception syphilis seroprevalence (PSS) and its distribution among this population may be able to help to eliminate MTCT. However, few population-based epidemiological studies have been focused on this group, and the association of DoM and age with PSS remains unclear. Methodology/Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Overall, 57.98% of the 7030 pregnant women included in this study were reproductive active period (25-35 years). The majority of the pregnant women included has education levels of junior high school or below, and their occupations were mainly farmers, which was consistent with the characteristic distribution of the syphilis population in China [18,19]. It…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Overall, 57.98% of the 7030 pregnant women included in this study were reproductive active period (25-35 years). The majority of the pregnant women included has education levels of junior high school or below, and their occupations were mainly farmers, which was consistent with the characteristic distribution of the syphilis population in China [18,19]. It…”
Section: Discussionsupporting
confidence: 72%
“…Overall, 57.98% of the 7030 pregnant women included in this study were reproductive active period (25–35 years). The majority of the pregnant women included has education levels of junior high school or below, and their occupations were mainly farmers, which was consistent with the characteristic distribution of the syphilis population in China [18, 19]. It was suggested that health education on syphilis prevention and control should focus on women in the reproductive active period and women of childbearing age in rural areas.…”
Section: Discussionmentioning
confidence: 60%
“…The detailed design, organization, and quality control have been published previously. 29,30 Briefly, there are 3 main phases in which detailed information was collected: preconception health examinations, early pregnancy follow-up, and…”
Section: Study Design and Populationmentioning
confidence: 99%
“…In the multivariable model, we additionally adjusted for maternal higher education (defined as senior high school, college, or higher; yes/no), preconception body mass index (BMI, continuous), diabetes (yes/no), preconception thyrotropin levels (continuous), ethnic origin (Han/others), household registration (rural/ urban), economic pressure (yes/no), smoking during pregnancy (yes/no), drinking during pregnancy (yes/no), passive smoking during pregnancy (yes/no), first gestation (yes/no), history of APOs (yes/no), and location (Pearl River Delta, East wing, West wing, or mountainous area). 30 The adjusted absolute risk differences (measured in percentage points) were calculated by marginal structural binomial regression models. 25 Inverse probability weights were computed using logistic models with the same covariates as the multivariable model predicting aRRs.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation